Dynamic investigation of hypoxia-induced L-lactylation - Jinjun Gao; Ruilong Liu; Kevin Huang; Ziyuan Li; Xinlei Sheng; Kasturi Chakraborty; Chang Han; Di Zhang; Lev Becker; Yingming Zhao (Proceedings of the National Academy of Sciences, 2025)
The recently identified histone modification lysine lactylation can be stimulated by L-lactate and glycolysis. Although the chemical group added upon lysine lactylation was originally proposed to be the L-enantiomer of lactate (K L-la ), two isomeric modifications, lysine D-lactylation (K D-la ) and N-ε-(carboxyethyl) lysine (K ce ), also exist in cells, with their precursors being metabolites of glycolysis. The dynamic regulation and differences among these three modifications in response to hypoxia remain poorly understood. In this study, we demonstrate that intracellular K L-la , but not K D-la or K ce , is up-regulated in response to hypoxia. Depletion of glyoxalase enzymes, GLO1 and GLO2, had minimal impact on K D-la , K ce , or hypoxia-induced K L-la . Conversely, blocking glycolytic flux to L-lactate under hypoxic conditions by knocking out lactate dehydrogenase A/B completely abolished the induction of K L-la but increased K D-la and K ce . We further observed a correlation between the level of K L-la and hypoxia-inducible factor 1 alpha (HIF-1α) expression under hypoxic conditions and when small molecules were used to stabilize HIF-1α in the normoxia condition. Our result demonstrated that there is a strong correlation between HIF-1α and K L-la in lung cancer tissues and that patient samples with higher grade tend to have higher K L-la levels. Using a proteomics approach, we quantified 66 K L-la sites that were up-regulated by hypoxia and demonstrated that p300/CBP contributes to hypoxia-induced K L-la . Collectively, our study demonstrates that K L-la , rather than K D-la or K ce , is the prevailing lysine lactylation in response to hypoxia. Our results therefore demonstrate a link between K L-la and the hypoxia-induced adaptation of tumor cells.